Calculated spectroscopic databases for the VAMDC portal: New molecules and improvements. (August 2020) - Richard, C.; Boudon, V.; Rotger, M.
Highlights: Calculated spectroscopic database. Major updates of existing databases of CH4 and C2 H4 . New databases built on the same model. Planetary and atmospheric applications. Graphical abstract: We present an important update of our previously existing calculated spectroscopic databases (CH4 and C2 H4 ), as well as new databases built on the same model (CF4, SF6, GeH4, RuO4 and SiF4 ). Abstract: We report the current status of our calculated spectroscopic relational databases. They contain line lists for specific molecules, that result from recently published spectroscopic analyses. The two original databases, denoted MeCaSDa (CH4 ) and ECaSDa (C2 H4 ), have been greatly improved with the addition of new calculated lines. Then, five new databases, TFMeCaSDa (CF4 ), SHeCaSDa (SF6 ), GeCaSDa (GeH4 ), RuCaSDa (RuO4 ) and TFSiCasDa (SiF4 ) were deployed based upon the same model. These databases are developed in the framework of the international consortium VAMDC (Virtual Atomic and Molecular Data Centre, http://vamdc.org ) and are also part of the Dat@OSU project (http://dataosu.obs-besancon.fr ).